2006
DOI: 10.1542/peds.2005-1325
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Cardiac Structure in Children

Abstract: OBJECTIVE. Epidemiologic studies have shown associations between impaired fetal growth and risk for coronary heart disease in adults. The underlying mechanisms are unknown. We investigated whether restricted intrauterine growth affects cardiac structure.METHODS. We performed echocardiography on 216 9-year-old children who were measured previously at birth. The diameter of the coronary left and right main branches was derived from the widest dimension; total coronary artery diameter was calculated by adding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
37
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 25 publications
8
37
1
4
Order By: Relevance
“…We have previously shown in adults that narrower retinal arterioles predict by many years the onset of clinical hypertension, 19 -21 diabetes mellitus, 31 and coronary heart disease, 22,23 which highlights the contribution of microvascular disease to these disorders. The present results thus complement and extend to small arterioles the substantial existing literature documenting associations of low birth weight with abnormalities of the large arteries such as reduced aortic dimension 14 and compliance, 13 increased wall thickening, 32 narrower coronary arteries, 33 and increased carotid atherosclerosis. 15,16 Smaller head circumference and shorter birth length are associated with higher blood pressure 9,34 and subsequent cardiovascular disease in adulthood, 10,35 and the present study is among the first, and the largest to date, to report associations of these birth parameters with structural abnormalities of the microcirculation.…”
Section: Discussionsupporting
confidence: 84%
“…We have previously shown in adults that narrower retinal arterioles predict by many years the onset of clinical hypertension, 19 -21 diabetes mellitus, 31 and coronary heart disease, 22,23 which highlights the contribution of microvascular disease to these disorders. The present results thus complement and extend to small arterioles the substantial existing literature documenting associations of low birth weight with abnormalities of the large arteries such as reduced aortic dimension 14 and compliance, 13 increased wall thickening, 32 narrower coronary arteries, 33 and increased carotid atherosclerosis. 15,16 Smaller head circumference and shorter birth length are associated with higher blood pressure 9,34 and subsequent cardiovascular disease in adulthood, 10,35 and the present study is among the first, and the largest to date, to report associations of these birth parameters with structural abnormalities of the microcirculation.…”
Section: Discussionsupporting
confidence: 84%
“…Low birthweight is known to be associated with narrower aortic, common carotid, 35 and coronary arteries. 10 Our study now shows that low birthweight is also associated with narrower resistance arterioles in addition to arteries. Importantly, we have previously demonstrated that retinal arteriolar narrowing is linked to a number of hypertension-related genes, 36 and prospectively predicts the development of hypertension 16,18 -20 and cardiovascular events such as coronary heart disease and stroke.…”
Section: Discussionsupporting
confidence: 52%
“…8 This led to the concept that fetal "programming" during critical phases of development in utero 2,9 may result in long-term structural changes in the vascular system. 10,11 However, the underlying vascular mechanisms are not known, but their elucidation is clearly important in further understanding the etiology of hypertension and cardiovascular disease. 12 It has been hypothesized that low birthweight may have an adverse impact on microcirculatory structure, 13,14 possibly initiating a cascade of arteriolar narrowing and vasoconstriction that ultimately leads to the development of hypertension.…”
mentioning
confidence: 99%
“…2,19,20 Discrepancy in the results may in part be explained by the smaller study cohorts and a wider age range in the previous studies. In a recent population-based prospective cohort study, LVM at the age of 2 years, however, increased with increasing birth weight in line with our results.…”
Section: Discussionmentioning
confidence: 85%